Uji Efek Analgetik Minyak Daun Cengkeh (Syzygium aromaticum) Terhadap Mencit Jantan Galur Balb/C - Wima Anggitasari (Jurnal Kesehatan dr. Soebandi, 2018)
Clove leaf (Syzygium aromaticum) is one of plant that is widely used as an alternative medicine community, one of the benefit of clove leaf is analgesic. Clove leaf oil is the part of clove leaf. The aim of the research to proved clove leaf oil has the analgesic activity. The data were analyzed with Kruskal-Wallis test, continuated by Mean-Whitney test with trust level 95%. This research was conducted with writhing reflex method with animal test of male mice Balb/C by 20 mice divided into 4 group.Group I as a control was treated with CMC Na 0,5% suspension, group II and III were treated with doses of 100 mg/kgBB and 200 mg/kgBB clove leaf oil, group IV was treated with aspirin. Number of streches (writhing reflex) was observed. The data were analyzed with KruskalWallis test, continuated by Mean-Whitney test with trust level 95%. This research of number of streches (writhing reflex) result significant difference between group I with group II, III and IV (p<0,005). Group II compare with III not significant difference (p>0,05). Group II compare with IV and group II compare with IV showed significant difference (p<0,05). The conclution of this research showed that clove leaf oil doses 100 mg/kgBB and 200 mg/kgBB has snalgesic activity